«Il Verbo si fece fratello»: l'ospitalità come paradigma dialogico in Christian de Chergé. - Territo, Luigi ca. 21. Jh. (Rassegna di teologia, 2026)
As a guest in the dār al-Islām (the house of Islam), Christian de Chergé lived a profound experience of hospitality, guided by his desire to be a "praying person among other praying people". The prior of Tibhirine promoted a "theology of dialogue" founded on listening and on the recognition of the action of the Spirit in every individual. De Chergé's legacy is not merely a model for interreligious dialogue, but a profound reflection on the nature of the human being and the mystery of God.